Zophobas morio larvae as a novel model for the study of Acinetobacter virulence and antimicrobial resistance - Rakovitsky, Nadya; Temkin, Elizabeth; Hameir, Amichay; Lurie-Weinberger, Mor; Keren-Paz, Alona; Carmeli, Yehuda (Frontiers in Microbiology, 2024)
The use of mammalian models for in vivo testing of bacterial virulence raises ethical concerns and is expensive and time-consuming. As an alternative, non-mammalian models are sought. Galleria mellonella larvae have been used as a model to study several bacterial pathogens. However, their maintenance is challenging, and commercial supply is low. In this study, we aimed to establish the Zophobas morio larvae as an alternative non-mammalian model for the evaluation of the pathogenicity and antimicrobial susceptibility of Acinetobacter baumannii. We infected Z. morio with Acinetobacter strains and determined the optimal temperature and inoculum. To visualize the bacterial distribution within the larvae, hematoxylin and eosin (H&E) staining was performed. Next, a survival model of infected larvae was established, and virulence was compared between strains. The effect of antimicrobial treatment in relation to antibiotic susceptibility was studied. Our results demonstrate that Z. morio can be used as a model system for in vivo studies of A. baumannii.